الموارد البشرية كألية لدعم تنافسة المؤسسات الاقتصادية - لعرابي, نسيمة (جامعة الوادي - University of Eloued, 2021)
يعيش العالم اليوم ديناميكية وحركية لا منتهية، حيث وضعت المؤسسة أمام التحديات المنافسة وهي مدى قدرتها على الحفاظ على حصتها السوقية والتهديدات بالزوال والاندثار، حيث تتحقق القدرة التنافسية لمؤسسات من خلال المعرفة والمهارات والقدرات المتوفرة في المورد البشري. وتعتبر تنمية الموارد البشرية على أساس تنافسية تجعلها مختلفة عن غيرها من حيث التخصص، الابتكار وتحديد طرق العمل وهناك طرق أخرى يمكن أن توضح دور الموارد البشرية في بناء القدرة التنافسية للمؤسسة ومنها: - القدرة على الابتكار والتطور والأداء الجيد لوظائفها؛ - زيادة القدرة الإنتاجية من خلال الاستغلال الأمثل للموارد بما في ذلك المورد الزمني. - إعطاء سمعة طيبة للمؤسسة من بيئتها الخارجية من خلال التعريف بها للغير وكذلك زيادة شهرتها بين العملاء والزبائن، وفي إطار العولمة واقتصاد السوق والمنافسة الحرة الذي لهم أثر كبير فأداء المؤسسة في إطار سياسة واضحة المعالم مدروسة الخطط كفيلة بتحقيق رؤية مستقبلية لمؤسسات اقتصادية ناجحة. The world today lives an endlessly dynamic and dynamic movement, as the institution has been placed in front of the competitive challenge which is the extent of its ability to maintain its market share and the threats of disappearing and disappearing, where the competitiveness of institutions is achieved through the knowledge, skills and capabilities available in the human resource. The development of human resources on a competitive basis makes them different from others in terms of specialization, innovationand identification of work methods. There are other ways that can clarify the role of human resources in building the competitiveness of the institution, including: - Capacity to innovate, develop and perform well. - Increase production capacity through optimal utilization of resources including time resource . - Giving the institution a good reputation from its external environment by introducing it to others as well as increasing its reputation among customers and customers, and in the context of globalization, market economy and free competition, which have a significant impact on the performance of the institution within the framework of a clearly defined policy studied plans to ensure the future vision of successful economic institutions .
Keywords: الموارد البشرية؛ الميزة التنافسية؛ القدرة التنافسية؛ القدرة على الابتكار؛ المؤسسة الاقتصادية.